Risk, discretion and stigma: a multi-level analysis of UK universities’ admissions policies and practices for people with a criminal record - Brooks, Charlotte Penelope (2025)
In the United Kingdom, there has been a rising interest in information pertaining to citizens’ criminal history, coupled with a lack of legal protection from discrimination for people with an unspent criminal record. This has paved the way for scholarship exploring the ‘collateral consequences’ of a criminal record. Yet beyond the field of employment, there is limited empirical evidence about the impact of a criminal record on access to civic opportunities. Using a mixed-method qualitative research design, this thesis investigates the impact of a criminal record on access to higher education in the United Kingdom. The findings are analysed using a multi-level conceptual framework, drawing on literature related to ‘risk’, ‘responsibilisation’, discretionary decision-making and stigma.